2016
DOI: 10.1177/0898010116642085
|View full text |Cite
|
Sign up to set email alerts
|

Embracing Our “Otherness”

Abstract: Theories on the importance of holistic and spiritual healing within nonconventional models of care are vast, yet there is little written about the practical, clinical-level interventions required to deliver such practices in collaborative cross-cultural settings. This article describes the learning experiences and transformative journeys of non-Indigenous nurse practitioners working with a Cultural Lead from an Indigenous community in British Columbia, Canada. The goal of the Seven Sisters Healthy Heart Projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The included studies specifically targeted the following diseases of focus: CVD; n = 8); heart health (n = 5); hypertension (n = 2); stroke (n = 2); coronary artery disease (n = 2); rheumatic fever (n = 1); or a combination of multiple chronic diseases (eg, CVD, diabetes; n = 1). 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 The aim of each study varied, in reflection of the following categories (note that some studies were identified as falling within multiple categories; Table 2 ): risk factor—understand discrepancies in or origins of heart health (n = 10); intervention—design/implementation of program or strategy (n = 9); and heart health management—Indigenous and/or Western approaches to manage heart health (n = 8). …”
Section: Resultsmentioning
confidence: 99%
“…The included studies specifically targeted the following diseases of focus: CVD; n = 8); heart health (n = 5); hypertension (n = 2); stroke (n = 2); coronary artery disease (n = 2); rheumatic fever (n = 1); or a combination of multiple chronic diseases (eg, CVD, diabetes; n = 1). 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 The aim of each study varied, in reflection of the following categories (note that some studies were identified as falling within multiple categories; Table 2 ): risk factor—understand discrepancies in or origins of heart health (n = 10); intervention—design/implementation of program or strategy (n = 9); and heart health management—Indigenous and/or Western approaches to manage heart health (n = 8). …”
Section: Resultsmentioning
confidence: 99%
“…Throughout the project, the NPs were challenged to balance Western traditional health promotion messages with indigenous healing ways. They navigated this experience as one of colearning, acknowledging differences, and allowing both worldviews to be present (Prodan-Bhalla et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of such interventions is dependent on the readiness of the community to work with outside health care establishments, on the openness of providers to embrace other perspectives, on the flexibility of the funders to support interventions that may evolve within the project time frame and may not report conventional or explicit top-down success indicators (Prodan-Bhalla et al, 2015), and on having an appropriate evaluation approach. Developmental evaluation (Patton, 2010) proved to be a valuable framework as it provided flexibility to redefine indicators and methodology as the project unfolded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations